ANALISIS FAKTOR DETERMINAN KUALITAS PELAYANAN PERSAMPAHAN DI KOTA PEMATANGSIANTAR* - Chandra Sihombing (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
The aim of this study is to know the garbage service quality in Pematangsiantar district pursuant to society as consumer perception, to identify and to know the determinant factors that influence the garbage service quality in Pematangsiantar district. This Research is done by using single variable that is service quality which consists of 5 (five) indicators. They are tangibles, reliability, responsiveness, assurance, empathy. The method that is used in this research is descriptive-quantitative approach, while data is collected technique through questionnaires, literature study/documentation, and interview. The questionnaires are propagated to the people of Pematangsiantar district that are spreading in 7 (seven) subdistricts which are totally 100 (hundred) respondents of 247.837 population in Pematangsiantar district. To determine determinant factor influencing the garbage service quality in Pematangsiantar district from existing dimension is done by using path analysis that calculates simultaneous path coefficient and furthermore calculates individually the each factor to determine most dominant factor.